Can Creativity Beat Death? A Review and Evidence on the Existential Anxiety Buffering Functions of Creative Achievement. (30th November 2016) - Perach, Rotem; Wisman, Arnaud
Abstract: The relationship between creativity and symbolic immortality had been long acknowledged by scholars. In a review of the literature, we found 12 papers that empirically examined the relationship between creativity and mortality awareness using a Terror Management Theory paradigm, overall supporting the notion that creativity plays an important role in the management of existential concerns. Also, a mini meta‐analysis of the impact of death awareness on creativity resulted in a small‐medium weighted mean effect. We examined the existential anxiety buffering functions of creative achievement as assessed by the Creative Achievement Questionnaire in a sample of 108 students. It was found that at high, but not low, levels of creative goals, creative achievement was associated with lower death‐thought accessibility under mortality salience in comparison to controls. To our knowledge, this is the first empirical report of the anxiety buffering functions of creative achievement among people for whom creativity constitutes a central part of their cultural worldview. The current findings support the notion that creative achievement may be an avenue for symbolic immortality, particularly among individuals who value creativity. Implications for understanding death‐related creativity motivations and their impact on individuals and society and for the promotion of creative achievement and creative motivation are discussed.